A closer look at the forgotten bones of the Dolmen of Pedras Grandes (Odivelas, Portugal). Examining old human remains 7 - Silva, Ana Maria (2021)
The Dolmen of Pedras Grandes (Odivelas, Lisboa, Portugal) was discovered and excavated at the end of the 19th century by Carlos Ribeiro. In 2004, this monument was re-excavated by Rui Boaventura and a complete study was conducted. The Dolmen of Pedras Grandes presents a polygonal chamber and a very short passage and may have had a short period of burial activity in the 4thmillennium as indicated by the radiocarbon dates and the “archaic” artefacts. The relative and absolute dating enable us to assign this monument to the initial phase of megalithic funerary monumentality in south-central Portugal. Moreover, the recovery of human skeletal material offers an opportunity to obtain data on the biological profile and the health status of the human community who buried their dead in this megalithic tomb. In this paper are present new radiocarbon dates and isotopic analyses obtained from human bone samples from this tomb and also a complete anthropological study of the human skeletal material recovered in this monument. At least 13 individuals are represented in the skeletal assemblage, including 8 adults (> 16 years) and 5 non-adults, although this is certainly an underestimate due to the poor preservation of the bone assemblage. Young children, under the age of three years, are missing. A small number of pathologies were observed, including cranial trauma, degenerative joint disease and oral pathologies. The high frequency of stress indicators, more specifically linear enamel hypoplasia, is a notable feature of this assemblage. The new data are discussed in the context of the problem of the origin of megalithic monumentality in Central and Southern Portugal.